Images du vieillir chez Wilkie Collins - Isabelle Hervouet-Farrar (Cahiers Victoriens et Edouardiens)
The study of three of Wilkie Collins’s novels : Mr Wray’s Cash-Box (1852), Armadale (1864-1866) and The Moonstone (1868) reveals that the character of the old man is an amalgamation of the image of the hero’s father and that of the hero. The old man is a source of anguish since he embodies the future and old age of a self doomed to go through his father’s early and debilitating physical degeneration. Taking into account how frequently Wilkie Collins endowed his characters with biographical details, we understand that whereas at the beginning of his literary career he easily managed to deny that the character of the old man was a representation of himself, such denial became increasingly difficult and summoned more complex strategies in the very popular novels of the 1860s. In The Moonstone, the process of debilitating degeneration is a clear feature of the character (Ezra Jennings) who appears as the projection of Wilkie Collins on the fictional scene.